Monetary policy, vagabonding liquidity and bursting bubbles in new and emerging markets: an overinvestment view - Gunther Schnabl; Andreas Hoffmann (Center for Economic Studies and ifo Institute (CESifo), 2007)
Credit booms have globally fuelled hikes in stock, raw material and real estate markets which have culminated in the recent US subprime market crisis. We explain the global asset market booms since the mid 1980s based on the overinvestment theories of Hayek, Wicksell and Schumpeter. We argue that ample liquidity supply originating in the large industrialized countries has contributed to overinvestment cycles in Japan, East Asia, the new markets in the industrial countries and many emerging market economies. Expansionary monetary policies in response to the burst of bubbles are argued to have contributed to vagabonding bubbles around the globe.
Keywords: B53; E32; E44; E52; 330; Vermögen; Bubbles; Gesamtwirtschaftliche Liquidität; Internationale Kapitalmobilität; Konjunkturtheorie; Finanzmarktkrise; Aufstrebende Märkte; Welt